Movement of two humpback whales (Megaptera novaeangliae) satellite-radio tagged off Eden, NSW and matched by photo-identification with the Hervey Bay catalogue - Franklin, Wally; Franklin, Trish; Andrews-Goff, Virginia; Paton, David; Double, Michael (J. Cetacean Res. Manage., 2023)
Photo-identification studies of humpback whales off eastern Australia show low levels of movement between eastern Australia and New Caledonia whales. Some eastern Australian humpback whales migrate through the southern waters of New Zealand on route to Antarctic feeding areas. Photoidentification studies have shown that the waters near the Balleny Islands, in Antarctic Area V, are a feeding area for some eastern Australian humpback whales. However, such studies provide no details of the routes taken between New Zealand and Australia and to and from Antarctic feeding areas. Sixteen humpback whales were satellite-linked radio tagged off Eden NSW in 2008. The number and duration of the tag positions reported revealed complete migratory transits from Eden to Antarctic Area V and IV feeding areas. Photographs of the Eden humpback whales were compared to the Hervey Bay photo-identification catalogue and yielded two matches, identified from lateral body marks and dorsal fins. This study provides the first evidence that during the southern migration some humpback whales stopover at Hervey Bay and also migrate past Eden on the NSW coast. The tracks of the two whales from Eden showed that a male sighted in Hervey Bay in the same season moved southeast from Eden towards southern New Zealand. A female with site-fidelity to Hervey Bay in previous seasons, accompanied by a calf when the tag was deployed, moved down and around the coast of Victoria, across Bass Strait and then southwest into the Antarctic Area IV feeding area. Eden may be a migratory hub for humpback whales departing from and approaching the east coast of Australia. This study suggests that eastern Australian humpback whales may exhibit a more diverse range of feeding destinations, after leaving Australian coastal waters, than previously reported.